Kajian Strukturalisme Levi-Strauss dalam Tradisi Bulusan sebagai Cerita Rakyat di Kudus, Jawa Tengah - Diki Wahyudi; Sahid Teguh Widodo; Firman Aziz; Wilma Silvia Y (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
This research is motivated by the existence of the annual tradition of Bulusan celebration as folklore in Kudus which is considered to have a structure. This study aims to describe the structures behind the Bulusan folklore in the Kudus community, Central Java. The formulation of the research problem is as follows: 1) Does the Bulusan folklore have a structure? 2) How is the transformation of the structure of the Bulusan folklore? This study uses a literature review method regarding various existing sources. The results of this study are as follows. 1) Bulusan story has a structure consisting of external structure, internal structure, and oppositional relations. 2) the transformation of the story is divided into six points, one of which is the Bulus transformation as a form of fertility and prosperity. Thus, this folklore about Bulus is relevant to be reviewed based on Levi Strauss structuralism analysis.